1981
DOI: 10.1007/bf00627922
|View full text |Cite
|
Sign up to set email alerts
|

Clinical pharmacokinetics of bezafibrate in patients with impaired renal function

Abstract: The pharmacokinetics of the new lipid-lowering drug bezafibrate has been investigated in patients with impaired renal function and hyperlipoproteinaemia. 12 patients received a single oral dose of bezafibrate 300 mg. Plasma and urine samples were collected and bezafibrate was analyzed by gas chromatography. Eight of the patients had moderately impaired renal function, with a creatinine clearance between 20 and 40 ml/min; the mean plasma half-life of bezafibrate in them was 7.8 +3.9 h (SD) and the plasma cleara… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

1982
1982
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 9 publications
0
12
0
Order By: Relevance
“…i protein lipase (Kraemer et al, 1982) and hepatic triglyceride lipase (Mordasini et al, 1977) (Anderson & Norbeck, 1981) and even with the reduced dosage employed in this study drug levels far in excess of this recommended level were attained.…”
Section: Significant Elevations In Serum Creatininementioning
confidence: 60%
See 1 more Smart Citation
“…i protein lipase (Kraemer et al, 1982) and hepatic triglyceride lipase (Mordasini et al, 1977) (Anderson & Norbeck, 1981) and even with the reduced dosage employed in this study drug levels far in excess of this recommended level were attained.…”
Section: Significant Elevations In Serum Creatininementioning
confidence: 60%
“…Serum levels of bezafibrate were determined by the manufacturer (Boehringer Mannheim Ltd, Germany) using a gas chromatography method (Endele, 1979) and the average steady state serum level calculated. The reduced dose of bezafibrate was chosen, as it has been shown that the drug half-life is prolonged in renal insufficiency (Anderson & Norbeck, 1981).…”
Section: Introductionmentioning
confidence: 99%
“…3. The straight regression line in this figure was calculated from data of Abshagen et al [2] and Anderson and Norbeck [5], demonstrating the influence of kidney function as judged by creatinine clearance on total clearance of bezafibrate. Nearly all of the values of the elderly are found unter the regression line.…”
Section: Resultsmentioning
confidence: 99%
“…The closer kinetics are in accordance with a one-compartment model, the less influence will be exerted by a change in total body clearance on apparent volume of distribution [18]. Elimination rate-corrected areas were also compared with literature data [1,3,5]. When comparisons between different bezafibrate preparations were made, i.e., normal-release and slow-release, data of the slowrelease preparations were corrected according to a bioavailability of 0.7 relative to the normal-release preparation (data not published).…”
Section: Pharmacokineticsmentioning
confidence: 99%
See 1 more Smart Citation